Effects of sodium arsenite in the modulation of testosterone synthesis by the hypothalamo-pituitary testicular axis and its effect on memory and learning in the rat - Ashraf, Saima (2018)
Sodium arsenite is a toxic metalloid that exists ubiquitously in the environment. Human exposure to arsenic compounds is a significant public health concern. In most populations, the main source of arsenic exposure is the drinking water. Chronic exposure to arsenic is associated with increased risks of various diseases. Recent emerging evidences suggest that arsenic exposure affects the reproductive and developmental toxicity that leads to the decrease of cognition by affecting on nervous system. The aim of this current research was to investigate the morphological changes in structure of testis, hormonal imbalance and effect on cognition in rats treated with different doses of sodium arsenite. Mature male Sprague Dawley rats at the age of 90 days were divided into 4 groups of 8 animals each. Group I received saline water whereas the other three groups received sodium arsenite at doses of 3, 5 and 8mg/kg of body weight of rats respectively, for 60 days by intraperitoneal injection. The blood samples were collected for follicle stimulating hormone (FSH), Luteinizing hormone (LH), testosterone and Brain-derived neurotrophic factor (BDNF) measurements at day 60. The Morris water maze (MWM) test was performed for spatial memory at day 60. Following this, the animals were then dissected and their testes were collected for histological studies. It was found that the effect of chronic exposure was dose dependent. A significant decrease (p≤0.05) was observed in plasma levels of testosterone, LH, FSH andBDNF in the higher dose groups (5mg/kg and 8mg/kg of body weight) in comparison to the control group. To characterize behavioural alterations induced by arsenic exposure, Morris water maze test was used. The Morris Water Maze test was performed for spatial memory at day 60. Following this, the animals were then dissected and their hippocampus was collected for histological studies. A significant decrease (p < 0.05) was observed in cognitive behaviour, during Morris water maze test, in the higher dose groups 5mg/kg and 8mg/kg) in comparison to the control group. Histological evaluation revealed dose-dependent, gradual damage in histoarchitecture of hippocampus. Moreover no significant change was observed in any experimental parameter in the low dose group (3mg/kg) in comparison to the control group. The results revealed that sub chronic exposure to sodium arsenite caused degenerative changes in hippocampus; decrease the level of BDNF and effects spatial memory in a dose dependent manner. Sodium arsenite exposure caused complete arrest of spermatogenesis with disrupted seminiferous tubules in the testes in high dose groups (5 and 8mg/kg). Moreover, no significant change was observed in any experimental parameter in the low dose group (3mg/kg of body weight) in comparison to the control group. Testosterone level was decreased by the exposure of sodium arsenite. Low levels of endogenous testosterone can be associated with poor performance on cognitive tests. For men with both cognitive impairment and low testosterone, testosterone substitution may be considered. Large, long- term studies evaluating the effects of testosterone substitution on cognitive function in older men and testosterone substitution on cognitive function in affected men exposed by sodium arsenite are warranted.